Comparison of Beinaglutide Versus Metformin for Weight Loss in Overweight and Obese Non-diabetic Patients - Gao, Lijun; Huang, Hong; Zhang, Lu; Zhang, Ningjing; Fu, Yuzhe; Zhu, Dalong; Bi, Yan; Feng, Wenhuan (Experimental and Clinical Endocrinology & Diabetes, 2021)
Purpose We compared the efficacy and safety of beinaglutide, a glucagon-like peptide-1 (GLP-1) analogue with metformin in lowering the bodyweight of patients who were overweight/obese and non-diabetic.Patients and Methods Seventy-eight non-diabetic patients were randomly selected and beinaglutide or metformin was administered for 12 weeks. The primary endpoints were changes in body weight and the proportions of patients who lost≥5 and≥10% of their baseline body weights.Results A total of 64 patients completed the study; patients in the beinaglutide group exhibited more bodyweight loss than those in the metformin group [(9.5±0.8%; 9.1±0.9 kg) and (5.1±0.9%; 4.5±0.8 kg), respectively, corresponding to a difference of approximately 4.5 kg (95% confidence interval, 2.2–6.9 kg; P<0.01)]. In the beinaglutide group, 90.6 and 40.6% of the patients lost≥5 and≥10% of their body weight, respectively, whereas, in the metformin group, these rates were 46.9 and 12.5%, respectively (P<0.01 and P<0.05). Weight loss following beinaglutide treatment mainly resulted from the loss of fat mass. Compared to metformin, beinaglutide induced a greater decrease in the body mass index, weight circumference, percent body fat, and body fat mass (total, trunk, limb, android, and gynoid). Additionally, beinaglutide decreased serum insulin levels and ameliorated insulin resistance.Conclusions Beinaglutide is more efficient than metformin at reducing weight and fat mass in patients who are overweight/obese and non-diabetic. Beinaglutide may be a useful therapeutic option for overweight/obesity control in the Chinese population.
Keywords: Glucagon-like peptide-1 receptor agonist; Biguanides; Weight loss ratio; Body composition